2018
DOI: 10.1186/s12906-018-2232-7
|View full text |Cite
|
Sign up to set email alerts
|

Hindering the formation and promoting the dispersion of medical biofilms: non-lethal effects of seagrass extracts

Abstract: BackgroundBiofilms have great significance in healthcare-associated infections owing to their inherent tolerance and resistance to antimicrobial therapies. New approaches to prevent and treat unwanted biofilms are urgently required. To this end, three seagrass species (Enhalus acoroides, Halophila ovalis and Halodule pinifolia) collected in Vietnam and in India were investigated for their effects in mediating non-lethal interactions on sessile bacterial (Escherichia coli) and fungal (Candida albicans) cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…However, it has been observed that biofilm-producing strains develop antibiotic resistance very fast, thus requiring the use of new antibacterial and antibiofilm compounds. Therefore, biofilms have a great impact on public health, causing about 65–80% of microbial diseases [ 107 ]. In this context, it has been reported that plant-derived extracts or isolated metabolites often exhibit good antibacterial and antibiofilm properties against several microorganisms.…”
Section: Flavonoids Involved In Antibiofilm Activitiesmentioning
confidence: 99%
“…However, it has been observed that biofilm-producing strains develop antibiotic resistance very fast, thus requiring the use of new antibacterial and antibiofilm compounds. Therefore, biofilms have a great impact on public health, causing about 65–80% of microbial diseases [ 107 ]. In this context, it has been reported that plant-derived extracts or isolated metabolites often exhibit good antibacterial and antibiofilm properties against several microorganisms.…”
Section: Flavonoids Involved In Antibiofilm Activitiesmentioning
confidence: 99%
“…Biofilm is a population of microbes attached to surfaces and sustained by the secretion of an adhesive and protective matrix; biofilms are prevalent in nature, medical and other environments. Due to their inherent tolerance and resistance to antimicrobials, they have enormous implications in healthcare-related infections [44]. The biofilms produced by pathogenic bacteria may cause many health complaints in human, like cystic fibrosis, prostatitis, and periodontitis [45].…”
Section: Discussionmentioning
confidence: 99%
“…The use of naturally derived plant-based extracts for antimicrobial and antibiofilm activity is steadily gaining traction in a variety of industries, not just due to their efficacious properties but also due to their less aggressive nature on sensitive surfaces and equipment when compared to sodium hydroxide, sodium hypochlorite, hydrogen peroxide, and other typical CIP treatments. A recent research article tested extracts from three species of sea grass ( Enhalus acoroides, Halophila ovalis, and Halodule pinifolia ) for their ability to prevent and remove clinically relevant biofilms [ 141 ]. All three leaf extracts showed a significant biofilm reduction capability against Escherichia coli and Candida albicans .…”
Section: Combating Biofilm: Potential Methodsmentioning
confidence: 99%